PENGARUH PROFITABILITAS, LIKUDITAS, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL PERUSAHAAN KONSUMEN PRIMER - Albert, Albert; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to find out how profitability, liquidity, and asset structure affect the capital structure of primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. The research sample was selected by purposive sampling method, and the valid data were 68 companies. The data in this study were processed using multiple linear analysis with the help of the Microsoft Excel 2017 program and IBM SPSS (Statistical Products and Services Solutions) Windows 27. The results of this study indicated that profitability, liquidity and asset structure had a significant negative effect on capital structure. The implications of this research are expected so that companies can consider the variables in this study in deciding capital structure policies.